Accumulation and Elimination of Cr in Gills and Eggs by the freshwater crab Zilchiopsis collastinensis after experimental exposure - Gagneten, Ana María (2008)
Cr accumulation and elimination were studied in the freshwater crab Zilchiopsis collastinensis (Crustacea, Decapoda) exposed to 3 (T1) and 6 (T2) mg CrVI/L using 1000-L tanks with dechlorinated water and artificial sediment. The objectives of this study were to analyze the Cr-accumulating capacity of Z. collastinensis males and females in gills and eggs, as well as to relate this capacity with crab weight, and to determine the Bioconcentration Factor (BCF) in relation to water and sediment. Significant differences in Cr concentration were found between the control and T1 and T2 (p = 0.018 and p = 0.001), and between T1 and T2 (p = 0.025). Significant differences in Cr concentration were found among all treatments in gills (p < 0.0001) and eggs (p = 0.0247), and when comparing Cr concentration between gills and eggs (p= 0.0046), but not between females and males (p = 0.6035). The tissues/water and tissues/sediment BCF values increased with Cr concentration, but was always higher in relation to water than to sediment. No relationship was found between crab weight and Cr concentration (r = -0.025). The obtained results constitute a great contribution to the knowledge of Cr accumulation in freshwater crabs. We propose Z. collastinensis as biomonitor of aquatic systems contaminated with Cr.